2009
DOI: 10.1371/journal.pone.0008497
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Population Structures of the Genes Encoding Ten Leading Vaccine-Candidate Antigens of the Human Malaria Parasite, Plasmodium falciparum

Abstract: The extensive diversity of Plasmodium falciparum antigens is a major obstacle to a broadly effective malaria vaccine but population genetics has rarely been used to guide vaccine design. We have completed a meta-population genetic analysis of the genes encoding ten leading P. falciparum vaccine antigens, including the pre-erythrocytic antigens csp, trap, lsa1 and glurp; the merozoite antigens eba175, ama1, msp's 1, 3 and 4, and the gametocyte antigen pfs48/45. A total of 4553 antigen sequences were assembled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
128
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 62 publications
18
128
2
Order By: Relevance
“…The identification of only two main sequence clusters shows that many of these PfRh2 haplotypes may be antigenically similar, and both of these were found among the PNG PfRh2 sequences that we obtained. This pattern of high within-population diversity for PfRh2 in this study was also found in several other merozoite Ags known to be important targets of host immunity (38,54). Merozoite Ags seem to have little regional diversification, but diversification has been observed for other Ags (38,54).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The identification of only two main sequence clusters shows that many of these PfRh2 haplotypes may be antigenically similar, and both of these were found among the PNG PfRh2 sequences that we obtained. This pattern of high within-population diversity for PfRh2 in this study was also found in several other merozoite Ags known to be important targets of host immunity (38,54). Merozoite Ags seem to have little regional diversification, but diversification has been observed for other Ags (38,54).…”
Section: Discussionsupporting
confidence: 76%
“…This pattern of high within-population diversity for PfRh2 in this study was also found in several other merozoite Ags known to be important targets of host immunity (38,54). Merozoite Ags seem to have little regional diversification, but diversification has been observed for other Ags (38,54). Our analysis did not clarify whether the observed changes occurred in PfRh2a or PfRh2b because the polymorphic region is contained within the common region of PfRh2.…”
Section: Discussioncontrasting
confidence: 50%
“…No blood-stage vaccine candidates have progressed beyond Phase II trials. Major challenges for subunit vaccines are the degree of antigenic polymorphism [8] and the need for a high antibody titer.…”
Section: Rationale For Attenuated Human Vaccines Targeting Malaria and mentioning
confidence: 99%
“…Typically, alleles from one or two reference strains (3D7 or FVO) are used in www.intechopen.com vaccine formulations, but this only partially represents the diversity of alleles circulating in the parasite population (Figure 1 [8]). Moreover, if vaccine alleles are found at low frequencies, the power to measure the success of vaccine trials is limited.…”
Section: Introductionmentioning
confidence: 99%
“…1. Worldwide frequency of alleles represented in ten leading malaria vaccine candidates (adapted from [8]). MSP1 19 3D7 and FVO are being developed as a combination vaccine as well as in isolation.…”
Section: Introductionmentioning
confidence: 99%